2022
DOI: 10.3390/ijerph19127170
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Seroprevalence and Factors Associated with Dengue Seropositivity in Petaling District, Malaysia

Abstract: Dengue virus (DENV) infection is a major public health concern, posing huge economic and disease burdens globally. In Malaysia, the incidence of DENV infections has increased significantly over the years. Nevertheless, the passive surveillance mechanism applied may not capture the actual magnitude of DENV infection. There was also a paucity of community-based studies exploring DENV seroprevalence. This study aimed to determine the DENV seroprevalence and the associated factors among the urban population in Pet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(80 reference statements)
2
5
0
Order By: Relevance
“…This could have been due to re-emergence of DENV3 after several years. 56,61,62 But the difference was not significant enough to confirm this hypothesis.…”
Section: Dengue Serotypingmentioning
confidence: 83%
See 1 more Smart Citation
“…This could have been due to re-emergence of DENV3 after several years. 56,61,62 But the difference was not significant enough to confirm this hypothesis.…”
Section: Dengue Serotypingmentioning
confidence: 83%
“…55 Nevertheless, the overall distribution of serotypes, from this study, was similar to other studies in Nepal, done during epidemic of 2022, where DENV1 was observed to be highly prevalent followed by DENV3. [56][57][58] Though Nepal has previously reported all four serotypes in the past, DENV1 and DENV2…”
Section: Dengue Serotypingmentioning
confidence: 99%
“… 59 2006–2012 A 0.034 (0.032, 0.036) Abbott Laboratories, Abbott Pakr, IL, USA Malaysia Petaling district 0-60+ 8 500 indirect IgG ELISA Ng et al. 60 Aug–Oct 2018 A 0.059 (0.052, 0.066) Panbio, Abbott, Chicago, IL, USA Malaysia Sungai Segamat 18–55+ 5 277 capture IgG ELISA Dhanoa et al. 61 Apr–May 2015 A 0.029 (0.025, 0.033) Panbio indirect and Capture elisa Alere, Brisbane, Queensland, Australia Malaysia forest areas of Peninsular Malaysia 0–13+ 2 491 capture IgG ELISA Abd-Jamil et al.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it is important to investigate the implications for reciprocal effects on DENV and ZIKV infection following YF vaccination or infection. Although our central hypothesis reflected the assumption that human flavivirus immunity, especially for DENV and ZIKV, is lower in Africa than in Asia or South America ( 32,3740 ), more data on seroprevalence in locations such as Angola, which recently experienced urban YF, would be useful. In addition, further studies utilizing African strains of YFV and African Ae.…”
Section: Discussionmentioning
confidence: 98%